Ruxolitinib‐combined doxorubicin‐etoposide‐methylprednisolone regimen as a salvage therapy for refractory/relapsed haemophagocytic lymphohistiocytosis: a single‐arm, multicentre, phase 2 trial. (9th February 2021) - Wang, Jingshi; Zhang, Rui; Wu, Xiaoyan; Li, Fei; Yang, Haixia; Liu, Ligen; Guo, Haixia; Zhang, Xuejun; Mai, Huirong; Li, Hui; Wang, Zhao
Summary: We performed a multicentre, non‐randomised trial (NCT03533790) to investigate the efficacy of ruxolitinib combined with the doxorubicin‐etoposide‐methylprednisolone (Ru‐DEP) regimen as a salvage therapy for refractory/relapsed haemophagocytic lymphohistiocytosis (HLH). All patients failing to achieve a complete or partial response 2 weeks after initial HLH‐94/HLH‐04 regimen or relapsed after remission were enrolled in the study between June 2018 and June 2019. The efficacy was evaluated 2 weeks after initiating Ru‐DEP salvage therapy. Fifty‐four eligible patients with refractory/relapsed (R/R) HLH were enrolled. One case could not be evaluated for efficacy. Excluding 12 patients who had previously received the DEP regimen, the overall response rate was 32 of 41 (78·0%) patients, with eight of 41 (19·5%) achieving complete response and 24 of 41 (58·5%) attaining a partial response. Of the R/R HLH patients who had previously received the DEP regimen, 7 of 12 (58·3%) achieved a partial response. Ferritin and soluble CD25 concentrations were significantly lower ( P < 0·05), while the platelet count increased significantly ( P = 0·034), and triglycerides decreased significantly ( P = 0·002) compared with those before treatment. The Ru‐DEP regimen may be a safe and effective salvage therapy, remaining effective in refractory/relapsed HLH following DEP treatment, especially in macrophage activation syndrome. In addition, the regimen can be considered for patients with contraindications to glucocorticoid, especially those with gastrointestinal bleeding.